Bronchodilator reliever use and its association with the economic and humanistic burden of COPD: a propensity-matched study. (2nd January 2017) - Punekar, Yogesh Suresh; Naya, Ian; Small, Mark; Holbrook, Tim; Wood, Robert; Mullerova, Hana; Valle, Manuel
Abstract: Background and aims: Short-acting bronchodilators are normally used as supplemental relief medication for breakthrough symptoms in COPD patients. The objective of this cross-sectional study was to assess if more frequent vs infrequent use of relief medication in maintenance-treated COPD patients, split by the severity dyspnea, was associated with an increase in the overall disease burden. Methods: A population-based cross-sectional survey (Adelphi DSP) was conducted among patients with COPD in five European countries. Information was collected on demographic and clinical characteristics, reliever inhaler use, dyspnea (mMRC), health status (CAT, EQ-5D), sleep quality (JSEQ) and healthcare resource use including moderate–severe COPD exacerbations, physician visits, COPD medications and other COPD related resources. The humanistic and economic burden was compared between patients with infrequent reliever use (<1 occasion/week) and more frequent use (≥ 1 occasion/week). The association between increased reliever use and economic burden was also examined after matching patients based on propensity-scores balancing demographic and disease burden characteristics. Results: Among the 1373 COPD patients prescribed a reliever inhaler, 29% reported using reliever medication ≥1 occasion/week. In the unmatched cohort, more frequent reliever use ( n = 377) compared to infrequent use ( n = 996) was linked to poorer health status (CAT: 25.7 vs 20.0; p < .0001; EQ-5D-3L: 0.63 vs 0.82; p < .0001) and poorer sleep quality (JSEQ: 8.6 vs 4.6 units; p < .0001). More frequent reliever use was also associated with higher annual rates of moderate/severe exacerbations (1.6 vs 1.0 events/year; p < .0001) and respiratory specialist visits (2.8 vs 2.2 events/year; p = .0001). In the propensity-score matched population, more frequent reliever use was also associated with significantly higher annual costs for COPD management (€5, 034 vs €3, 705, p = .0327) compared to patients with infrequent reliever use. Conclusion: In moderate-to-severe COPD, more frequent reliever use is associated with increased exacerbation risk and increased management costs.